An integrated optimization framework for multi-cycle environmental stress screening tests and preventive maintenance scheduling. (October 2017) - You, Ming-Yi
An integrated optimization framework for multi-cycle environmental stress screening tests and preventive maintenance scheduling is proposed. The proposed framework considers the improvement of product reliability through environmental stress screening tests and the associated screening cost, and the effect of preventive maintenance schedule on the maintenance cost as well. The environmental stress screening model is extended first to be applicable for multi-cycle environmental stress screening tests. The extended environmental stress screening model characterizes the product reliability function which survives the environmental stress screening test in terms of both the number of environmental stress screening cycles and the severity of screening stress. Afterwards, an integrated cost model is established by considering the cost of preventive maintenance, the cost of corrective maintenance, the cost of environmental stress screening test, and the cost due to failure of products in the environmental stress screening test. The application case study demonstrates the implementation procedures and the application effectiveness of the proposed approach. The application results show that, considering the cost due to environmental stress screening and the cost due to maintenance separately could lead to suboptimal decisions. For enterprises responsible for both environmental stress screening and maintenance, it is suggested to optimize the environmental stress screening test and maintenance scheduling jointly to minimize the overall cost.